AN ANALYSIS OF HUMOR SPEECH ACT OF THE BIG BANG THEORY AT CBS TELEVISION SERIES - Suardi, Suardi (Universitas Gunadarma, 2020)
Some of the problems faced by students in learning English are speech acts. This research focused on finding the speech acts. This study aims to get an overview of humor speech acts of the big bang theory. The qualitative descriptive approach will be used along with the content analysis technique. The result shows that: (1) there are three parts of speech acts used, including locutionary, illocutionary, and perlocutionary acts, (2) there is a violation of quantity, quality, relevance, and manner maxim. However, the most violation maxim was at the quantity maxim, (3) the screenwriters intentionally create a dialogue with several principles’ violations of speech acts, team-works, and humor categories. It can be concluded that the speech acts humor of the big bang theory screenwriters intentionally made some mistakes to create humor to raise up the jocularity atmosphere that can be enjoyed by the viewers. It is expected that this research can enrich the knowledge as regard the linguistic phenomena especially those which are related to speech acts.